Significant association between perceived HIV related stigma and late presentation for HIV/AIDS care in low and middle-income countries: A systematic review and meta-analysis - Gesesew, Hailay Abrha; Tesfay Gebremedhin, Amanuel; Demissie, Tariku Dejene; Kerie, Mirkuzie Woldie; Sudhakar, Morankar; Mwanri, Lillian (PLOS ONE, 2017)
Background Late presentation for human immunodeficiency virus (HIV) care is a major impediment for the success of antiretroviral therapy (ART) outcomes. The role that stigma plays as a potential barrier to timely diagnosis and treatment of HIV among people living with HIV/AIDS (acquired immunodeficiency syndrome) is ambivalent. This review aimed to assess the best available evidence regarding the association between perceived HIV related stigma and time to present for HIV/AIDS care. Methods Quantitative studies conducted in English language between 2002 and 2016 that evaluated the association between HIV related stigma and late presentation for HIV care were sought across four major databases. This review considered studies that included the following outcome: ‘late HIV testing’, ‘late HIV diagnosis’ and ‘late presentation for HIV care after testing’. Data were extracted using a standardized Joanna Briggs Institute (JBI) data extraction tool. Meta- analysis was undertaken using Revman-5 software. I2 and chi-square test were used to assess heterogeneity. Summary statistics were expressed as pooled odds ratio with 95% confidence intervals and corresponding p-value. Results Ten studies from low- and middle- income countries met the search criteria, including six (6) and four (4) case control studies and cross-sectional studies respectively. The total sample size in the included studies was 3,788 participants. Half (5) of the studies reported a significant association between stigma and late presentation for HIV care. The meta-analytical association showed that people who perceived high HIV related stigma had two times more probability of late presentation for HIV care than who perceived low stigma (pooled odds ratio = 2.4; 95%CI: 1.6–3.6, I2 = 79%). Conclusions High perceptions of HIV related stigma influenced timely presentation for HIV care. In order to avoid late HIV care presentation due the fear of stigma among patients, health professionals should play a key role in informing and counselling patients on the benefits of early HIV testing or early entry to HIV care. Additionally, linking the systems and positive case tracing after HIV testing should be strengthened.